2012
DOI: 10.1242/jcs.094573
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy plays an essential role in the clearance of Pseudomonas aeruginosa by alveolar macrophages

Abstract: SummaryIntracellular bacteria have been shown to cause autophagy, which impacts infectious outcomes, whereas extracellular bacteria have not been reported to activate autophagy. Here, we demonstrate that Pseudomonas aeruginosa, a Gram-negative extracellular bacterium, activates autophagy with considerably increased LC3 punctation in both an alveolar macrophage cell line (MH-S) and primary alveolar macrophages. Using the LC3 Gly120 mutant, we successfully demonstrated a hallmark of autophagy, conjugation of LC3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
183
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(190 citation statements)
references
References 49 publications
7
183
0
Order By: Relevance
“…3,4,18,19 Infection with this bacterium also initiates autophagy. 17,20 We found that inhibition of autophagy upregulated inflammasome activation following P. aeruginosa infection. This was due to autophagy removing damaged mitochondria that released mitochondrial DNA following infection in a process dependent on production of reactive oxygen intermediates.…”
Section: Introductionmentioning
confidence: 92%
“…3,4,18,19 Infection with this bacterium also initiates autophagy. 17,20 We found that inhibition of autophagy upregulated inflammasome activation following P. aeruginosa infection. This was due to autophagy removing damaged mitochondria that released mitochondrial DNA following infection in a process dependent on production of reactive oxygen intermediates.…”
Section: Introductionmentioning
confidence: 92%
“…Autophagy or autophagic protein exerts its role in host defense by degrading various clinically important pathogens in the lysosome. The target pathogens include bacteria such as Mycobacterium tuberculosis (35), Pseudomonas aeruginosa (194), group A Streptococcus pyogens (119), Shigella flexneri (117), Salmonella enterica (19,185), and Listeria monocytogenes (196), virus such as herpes simplex virus type 1 (HSV-1) (191), and parasites such as Toxoplasma gondii (196).…”
Section: Role Of Autophagy In Microbial Clearancementioning
confidence: 99%
“…Finally, the autophagosome fuses with the lysosome, forming an autolysosome, where the cargo is digested by lysosomal enzymes and the degraded material released into the cytoplasm for recycling by the cell. macrophages and their response to different stimuli, 22,24,25 thus highlighting the connections among autophagy, macrophages, and cancer, and suggesting the potential to enhance an antitumor response by modulating autophagy in macrophages. Given the major roles of macrophages and autophagy in tumor progression and their correlation in biological activities, it is valuable to clarify the contribution and underlying molecular mechanisms of autophagy-mediated regulation of macrophages, and their implications for cancer.…”
Section: Introductionmentioning
confidence: 99%